Cutoff value for predicting success in triathlon mixed team relay - Ledanois, T.; Hamri, I.; De Larochelambert, Q.; Libicz, S.; Toussaint, J. F.; Sedeaud, A. (Frontiers in Sports and Active Living, 2023)
Introduction The Mixed-Team-Relay (MTR) triathlon is an original race format present on the international scene since 2009, which became an Olympic event at the Tokyo 2020 Games. The aim of this study was to define the probabilities of reaching a victory, a podium, or a finalist rank in a relay triathlon, according to the position of any of the four relayers (Women/Men/Women/Men) during each of the four segments (leg) of the race. Methods All MTR results from the World Series, Continental Championships, World Championships from 2009 to 2021 and Tokyo 2020 Olympics have been collected. We calculated the set of probability frequencies of reaching a given final state, according to any transient state during the race. All results are compared with a V' Cramer method. Results The frequency of winning is similar at the end of Leg 1 for TOP1 (first position) and TOP2-3 (second and third positions). Then, a difference in the winning-associated frequencies is first observed after the Bike stage of Leg 2, where 47% of TOP1 athletes will win, vs 13% of the TOP2-3. Discussion This difference continually increases until the end of the race. Legs 2 and 3 are preponderant on the outcome of the race, the position obtained by each triathlete, especially in swimming and cycling, greatly influences the final performance of the team. Leg 1 allows to maintain contact with the head of the race, while Leg 4 sets in stone the position obtained by the rest of the team.